2002
DOI: 10.1542/peds.110.1.e4
|View full text |Cite
|
Sign up to set email alerts
|

No Evidence of Autoimmunity in 6-Year-Old Children Immunized at Birth With Recombinant Hepatitis B Vaccine

Abstract: ABSTRACT. Objectives. Taking into account that genetic predisposition, marked by human leukocyte antigen (HLA) class I and II genes, augments the probability of developing an autoimmune disorder after a triggering vaccination, as largely debated, we investigated the frequency of autoantibody production after recombinant hepatitis B vaccine (rHBv) in 6-year-old children immunized at birth to evaluate an association between autoimmune disorders and hepatitis B virus vaccination.Methods. We investigated the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
5

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 28 publications
1
15
0
5
Order By: Relevance
“…It was recently suggested that polyreactive antibodies would be more effective at neutralizing HIV-1 due to polyreactivity-mediated heterotypic binding to virions (37,38). Whether the induction of polyreactive antibodies by vaccination, such as observed in the present study, will aug- (19,53), while no longterm adverse effects were reported (6,54). Using techniques similar to those employed in this study, we found that ϳ20% of isolated rMAbs from subjects immunized with trivalent inactivated influenza vaccine were polyreactive (B. F. Haynes, unpublished data).…”
Section: Discussionsupporting
confidence: 48%
“…It was recently suggested that polyreactive antibodies would be more effective at neutralizing HIV-1 due to polyreactivity-mediated heterotypic binding to virions (37,38). Whether the induction of polyreactive antibodies by vaccination, such as observed in the present study, will aug- (19,53), while no longterm adverse effects were reported (6,54). Using techniques similar to those employed in this study, we found that ϳ20% of isolated rMAbs from subjects immunized with trivalent inactivated influenza vaccine were polyreactive (B. F. Haynes, unpublished data).…”
Section: Discussionsupporting
confidence: 48%
“…A brief review of the medical literature reveals multiple infectious agents that are believed to contribute to the development of CD in susceptible patients. Among the best studied are adenovirus type 12 15–21 and hepatitis C virus (HCV) 22–25 . Other infectious agents, described mainly in case reports, include Campylobacter jejuni, Giardia lamblia , rotavirus, and enterovirus 26–28 …”
Section: Discussionmentioning
confidence: 99%
“…This was an embarrassment to the French public health authorities who had banned the vaccine based on public pressure and anti-vaccine fears of an association, rather than scientific data. No scientific association has been reported between hepatitis B virus vaccination and severe autoimmune diseases such as multiple sclerosis [36,39].…”
Section: Vaccines and Autoimmunitymentioning
confidence: 99%